2020
DOI: 10.1172/jci.insight.138724
|View full text |Cite
|
Sign up to set email alerts
|

The value of genotypic and imaging information to predict functional and structural outcomes in ADPKD

Abstract: BACKGROUND. A treatment option for autosomal dominant polycystic kidney disease (ADPKD) has highlighted the need to identify rapidly progressive patients. Kidney size/age and genotype have predictive power for renal outcomes, but their relative and additive value, plus associated trajectories of disease progression, are not well defined. METHODS. The value of genotypic and/or kidney imaging data (Mayo Imaging Class; MIC) to predict the time to functional (end-stage kidney disease [ESKD] or decline in estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…When patients were stratified according to disease severity reflected by the MIC, those with the most severe disease (MIC 1E patients) had fully penetrant PKD mutations (92%) and were predominately men (70%). This suggests that PKD mutation strength and male gender are major determinants of rapid cystic expansion and is consistent with the results of the CRISP study 5 , 6 and the aggravating effect of testosterone in several rodent models of PKD. 26 , 27 , 28 , 29 In contrast, most patients with ESKD with class MIC 1B or 2B were women (82%) with fewer fully penetrant PKD mutations (55%).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…When patients were stratified according to disease severity reflected by the MIC, those with the most severe disease (MIC 1E patients) had fully penetrant PKD mutations (92%) and were predominately men (70%). This suggests that PKD mutation strength and male gender are major determinants of rapid cystic expansion and is consistent with the results of the CRISP study 5 , 6 and the aggravating effect of testosterone in several rodent models of PKD. 26 , 27 , 28 , 29 In contrast, most patients with ESKD with class MIC 1B or 2B were women (82%) with fewer fully penetrant PKD mutations (55%).…”
Section: Discussionsupporting
confidence: 88%
“…Understanding the characteristics associated with age of ESKD onset is critical, given its implication on modifying the disease course. Despite the phenotypic variability, observational studies of large ADPKD cohorts, including CRISP 5 , 6 , 7 , 8 and pooled registry datasets, 24 , 25 have shown that HtTKV strongly predicts the risk of GFR decline and progression to ESKD. The number of patients who reached ESKD in these cohorts was relatively low at the time of analysis (42 [18.6%] and 88 [5.4%]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations